Proteomic analyses of mitochondrial damage in postmortem beef muscles. (26th January 2022) - Liu, Chunmei; Wei, Qichao; Li, Xia; Han, Dong; Liu, Jiqian; Huang, Feng; Zhang, Chunhui
Abstract: BACKGROUND: The objective of the study was to examine the expression profiles of mitochondrial proteins in at‐death and 24 h postmortem (PM) using tandem mass tag (TMT) approach to characterize the mitochondria possible mechanisms that are affiliated with tenderization. RESULTS: Results showed that the tender meat at 24 h PM emerged with more serious mitochondrial damage. Altogether 456 mitochondrial proteins were identified, including 442 down‐regulated and 14 up‐regulated proteins. These differentially‐expressed proteins were primarily involved in the progress of PM energy metabolism, apoptosis, and the morphological alterations of mitochondrial. Among them, 47 subunits (such as NDUFA2, COX4I1, and ATP5PB) were annotated into the oxidative phosphorylation pathway. VDAC1, VDAC2, and VDAC3 involving in the damage of MPTP, and IMMT, CHCHD3, APOL and APOO modulating the morphology of mitochondria, and DIABLO and AIFM1 released from mitochondria affect caspase's activation. HSPD1 and HSPE1 involved in apoptosis, mitochondrial physiological and morphological alterations. CONCLUSION: The earlier‐mentioned proteins were validated as potential indicators of tenderness regulated by mitochondrial damage. These results highlighted that mitochondrial damage possibly participate in PM tenderization of beef muscles by energy metabolism and cell apoptosis status. © 2022 Society of Chemical Industry.